2017
DOI: 10.1177/1055665617718825
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Orthodontic Burden of Care in Patients With Unilateral Complete Cleft Lip and Palate

Abstract: Objective: To assess the orthodontic burden of care of patients from a Brazilian rehabilitation center (Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo [HRAC-USP]). Design: Retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…Inefficiencies and barriers to care access are coupled with the labor-intensive process of palatal expansion and phase-1 orthodontics for patients with cleft lip and palate (Alberconi et al, 2018; Hameed et al, 2019). It may be quite difficult for families with limited resources to find a capable orthodontist who is geographically convenient and accepts their insurance, not to mention to attend regular orthodontic appointments to complete care in a time-sensitive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Inefficiencies and barriers to care access are coupled with the labor-intensive process of palatal expansion and phase-1 orthodontics for patients with cleft lip and palate (Alberconi et al, 2018; Hameed et al, 2019). It may be quite difficult for families with limited resources to find a capable orthodontist who is geographically convenient and accepts their insurance, not to mention to attend regular orthodontic appointments to complete care in a time-sensitive manner.…”
Section: Discussionmentioning
confidence: 99%
“…This was done in order to adjust to the fact that all patients had already been recruited in the study when the pain questionnaires were completed; therefore, acute initial pain would have been mostly referred as a past experience with the additional bias of painkillers intake. Given the high burden of orthodontic care in patients with CLP and in patients affected by CFA (Meazzini et al, 2015; Alberconi et al, 2018), we were especially interested in the “burden of orthodontic pain” felt by these patients.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors reported that patients wearing Invisalign experienced less pain during treatment and took less pain medications compared to patients wearing braces (Miller et al, 2007; Fujiyama et al, 2014; White et al, 2017; Almasoud, 2018), while others found no statistically significant differences in the pain levels (Shalish et al, 2012; Noll et al, 2017). Few articles have taken specifically in consideration the burden of care of orthodontic treatment in cleft patients (Meazzini et al, 2015; Alberconi et al, 2018), and none have considered their burden in terms of pain perceived. Given the multiple choices in orthodontic techniques, the objective of this study was to compare, in a prospective case–control study, the difference in pain perception between treatment with AL and traditional orthodontics in patients affected by cleft and craniofacial anomalies (CFA).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, individual interventions have been assessed for the impact on burden of care. Alberconi et al (2018) assessed the burden of care of orthodontic treatment in patients with unilateral complete cleft lip and palate by considering mean time of treatment, number of appointments, mean number of appliances, mean number of surgical procedures, and mean distance traveled to appointments. Attempts to quantify this burden have also been studied particularly for NAM, including an assessment of factors influencing completion and noncompletion of NAM (Dean et al, 2019).…”
Section: Introductionmentioning
confidence: 99%